Awareness, attitude and practice on contraception among the clients attending abortion service at a zonal hospital (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Contraceptive methods are important components to reduce unwanted pregnancy, abortion, maternal and child morbidity mortality. This study aim to identify awareness, attitude and practice on contraception among women attending abortion services at Seti Zonal Hospital, Nepal.Method: Cross-sectional enumeration sampling techniques from Safe abortion Unit of Seti Zonal Hospital, Nepal, from August to September 2018 was taken for structured face to face interview using questionnaire to find out awareness, attitude and practice on contraception among women. Ethical approval was obtained. The SPSS version 16 was used to analyze data.Result: Out of total 94 women, 59 (73.8%) had adequate awareness, 78 (83%) had positive attitude for use of contraception, 44 (46.8%) had inadequate practice of contraception and 19 (20.2%) had adequate practice. There was a significant association between types of family and level of awareness (P